PENGARUH KONSENTRASI AGAR-AGAR TERHADAP KUALITAS KIMIA DAN HEDONIK PERMEN JELLY BELIMBING WULUH (Averrhoa blimbi L): The Effect of Gelatine Concentration on the Chemical and Hedonic Quality of Jelly Candy Belimbing Wuluh (Averrhoa Bilimbi L) - Novi Dwi Fatmawati, Restiani Sih Harsanti, Arfiati Ulfa Utami (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2022)
Jelly candy is a food product that is liked by toddlers to adults. Belimbing wuluh has the potential to be used as a basic ingredient to make jelly candy because it contains 5% pectin of the dry weight. Although there are pectins from fruit extract, adding other gelling agents is necessary to produce a great jelly candy texture. This research aimed to identify the effect of the agar concentration on the chemical and hedonic quality of belimbing wuluh jelly candy and to determine the optimum agar concentration of agar to produce the best belimbing wuluh jelly candy. The research design used a completely randomized design (CRD) consisting of 6 treatments, such as P1 (6 grams), P2 (9 grams), P3 (12 grams), P4 (15 grams), P5 (18 grams and P6 (21 grams) and 4 replication. Data were analyzed using ANOVA and continued with DMRT 5% test the hedonic test continued with the De Garmo test. The result showed that the concentration of agar has no significant effect on water content, but has a significant effect on pH, elasticity, stickiness, texture, color, and taste of belimbing wuluh jelly candy. Based on the results of de Garmo’s analysis, the best treatment was P2 with the addition of concentration 9 grams agar.